A Literature Review: Potential Ethical Risk in Mental Health Research at Workplace Setting - Era Nurissama; Ray Wagiu Basrowi (ILUNI MKK FKUI and PRODI MKK FKUI, 2025)
Introduction: Research on mental health in the workplace presents a complex ethical landscape due to the dual relationships and power dynamics inherent in employer-employee interactions. Workers may feel pressured to participate in research due to real or perceived pressure from their employer, which may affect the voluntariness of their consent. The aim of this review is to describe ethical issues in informed consent related in mental health research interventions in the workplace. Methods: We conducted a search at the Google Scholar database in May 2024, examining various publications and journals from the past five years related to ethical issues surrounding informed consent for mental health research in the workplace using the keywords: informed consent, mental health, ethics, workplace. Results: Total of 3 journals as literature review. Significant impacts from such stigma and discrimination were found in all the journal. Disclosed mental health situation increased a positive impact result at workplace eventough the outcome is infuenced by many factors. The findings indicate a need to provide support mechanisms and to change the culture of workplaces to improve employment opportunities and outcomes for people living with mental health problem. Conclusions: Ensuring ethical informed consent in mental health research within workplace settings requires careful consideration of confidentiality, voluntariness, and transparency. Addressing these issues through multi-stakeholder engagement and fostering a supportive organizational culture can enhance ethical standards. Future research should continue to explore these dynamics and develop strategies to protect participants’ rights and well-being.